Rappresentazione naturale e simbolica in Tommaso d’Aquino. Alcune note - Fabrizio Amerini (Aisthesis, 2018)
Talking of “medieval aesthetics” is historiographically disputable. During the Middle Ages, in fact, there is no discipline comparable with the aesthetics as from the eighteenth century we know it. In the medieval period, aesthetic considerations mostly occur in spurious contexts, and are all, so to say, pre-theoretical. They refer to different insights on what is the beautiful (pulchrum) and what relationship holds between the beauty (pulchritudo) and its artistic expression. In the Middle Ages, that is, one can frequently encounters forms we would nowadays call of descriptive aesthetics, occasionally forms of normative aesthetics, rather sporadically meta-aesthetic considerations. Not even a privileged attention is reserved to aesthetics understood as the description of the conditions of pleasure that follow from the perception of the beautiful, despite the theme of dilectum is important in the aesthetic meditations of medieval masters. Aesthetic discussions predominantly concern the relationships between the artist, an object and its representation (especially pictorial). In this essay, I reconsider these relationships by discussing a key point of Thomas Aquinas’s reflection on the beauty: the role played by of the notion of representation in the explanation of the artistic process.